2022
DOI: 10.1016/j.jgr.2022.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng, a promising choice for SARS-COV-2: A mini review

Abstract: The current Covid-19 pandemic has changed the entire world and bought so many unprecedented challenges to the scientific community. More than 5 million people died due to the SARS-COV-2 outbreak. For many thousands of years, ginseng, the traditional herb has been used for various infectious diseases by traditional healers. Ginseng showed promising antiviral effects by modulating both natural and acquired immunity. Ginseng might be used as a potential therapeutic agent to prevent SARS-CoV-2 infection along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“… 13 , 14 , 15 , 16 Ginseng was reported as a promising adjuvant for the treatment of viral diseases such as SARS-CoV-2. 17 , 18 Regarding their antiviral activities, Ginseng can inhibit, or show protective effects against a range of viruses such as Hepatitis B, Human Rotavirus, H5N1 influenza virus, H1N1 influenza A virus and respiratory syncytial virus (RSV). 17 A formula containing both Ginseng and Notoginseng has been used in the recovery phase for DENV-infected patients in China.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 , 15 , 16 Ginseng was reported as a promising adjuvant for the treatment of viral diseases such as SARS-CoV-2. 17 , 18 Regarding their antiviral activities, Ginseng can inhibit, or show protective effects against a range of viruses such as Hepatitis B, Human Rotavirus, H5N1 influenza virus, H1N1 influenza A virus and respiratory syncytial virus (RSV). 17 A formula containing both Ginseng and Notoginseng has been used in the recovery phase for DENV-infected patients in China.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have evaluated and published their anti-viral (COVID-19) efficacy. 22,23 Therefore, this study evaluated the anti-viral effectiveness of ginsenosides (122) via computational approaches, as they are the principle and fundamental investigation methodology that has been used widely in recent times. Computational techniques are vital to discover novel and potential small molecules in drug discovery and development as they are cost-, time-, and labor-effective.…”
Section: Resultsmentioning
confidence: 99%
“…Since the beginning of the pandemic, numerous in silico studies highly focus on screening and repurposing potential inhibitors from natural products for their anti-viral efficacy against SARS-CoV-2. [15][16][17][18][19][20][21][22][23] Natural products such as plant metabolites comprise a vast and diverse source of bioactive compounds, some of which are supported by thousands of years of traditional medicine. Because of their varied therapeutic applications, one among them is "ginsenosides," major bioactive components of Panax ginseng, family Araliaceae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its anti-viral properties, in particular, is considered a feature of Ginseng Radix et Rhizoma and its extracts in viral-induced fatigue, which distinguishes it from other ME/CFS—such as postoperative, cancer, or other pathogen-related fatigue. Several studies have reported that oral administration of Ginseng Radix et Rhizoma extracts shows promising anti-viral effects (e.g., lowering viral loads and improving the viability of infected cells) against human immunodeficiency virus-1, influenza virus, rotavirus, and respiratory syncytial virus [ 25 26 ] . Ginseng Radix et Rhizoma can ameliorate chronic inflammation induced by a variety of autoimmune diseases—such as rheumatic diseases and inflammatory bowel disease—presumably by inhibiting the release of inflammatory cytokines, such as IL-6 and TNFα [ 27 28 ] .…”
Section: Underlying Mechanisms Of Anti-fatigue Effects Of G...mentioning
confidence: 99%